The Influence of Using Audio-lingual Method on Students’ Speaking Skill in Madrasah Diniyah Takmiliyah Awwaliyyah - Aprianto Aprianto; Mahyudin Ritonga; Yoni Marlius; Raihan Nusyur (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2020)
The study aimed to determine the influence of audio-lingual methods towards the Arabic speaking skills, the method used in this research was quantitative with experimental quasi approach, data collection technique was polling and test. The population of this research was 102 students in the MDTA Bustanul Huda at Padang City, West Sumatera, Indonesia. Data obtained through polls and tests were then analyzed statistically. The analysis used the normality test, homogeneity test, and hypothesis test. All three types of tests were done with the help of the SPSS Statistics 22 program. The results of the study were: 1) the use of audio-lingual methods was categorized on good classification with an average of 63.33 in intervals 62-64; 2) Speaking Arabic skills was categorized on good classification with an average of 68 in intervals 65-68; and 3) the score of influence with N 30 obtained sig α 0.001 and the score of r Square 0.35. There was a significant influence between the use of audio-lingual methods to the Arabic speaking skill of students at MDTA Bustanul Huda Ulak Karang at Padang City Indonesia in the academic year 2019/2020. The influence of variable X to variable Y because students are accustomed to hearing how to speak Arabic as the native speaker of the Arabic language.